In Silico Analysis of Limonoid-Based Antifeedants from Melia volkensii Targeting the Ryanodine Receptor in Spodoptera frugiperda - Rajab, Mohamed Said (Sciences of Phytochemistry, 2024)
Spodoptera frugiperda is an invasive pest causing significant crop losses worldwide. Resistance development and health and environmental concerns associated with synthetic insecticides have prompted a search for eco-friendly biopesticides. Limonoids such as salannin, volkensin, and volkensinone, isolated from the East African plant Melia volkensii, show antifeedant activity against S. frugiperda larvae. Volkensin had an ED50 of 3.5 µg/cm², volkensinone (a lactone of volkensin) an ED50 of 6 µg/cm², and salannin an ED50 of 13 µg/cm². Additional limonoids from M. volkensii, including salanninolide and toosendanin, also displayed strong antifeedant effects. With toosendanin already used commercially, a re-evaluation of M. volkensii antifeedant compounds was conducted using in silico techniques. Docking simulations with 3D models of these limonoids and the S. frugiperda ryanodine receptor protein revealed binding affinities from -6.4 to -7.5 kcal/mol, comparable to those of chlorantraniliprole, a commercial insecticide targeting ryanodine receptors. These binding affinities at two distinct receptor sites align well with in-vitro antifeedant activity, underscoring M. volkensii’s potential for environmentally friendly, receptor-targeted biopesticide development against S. frugiperda.